Soliton solutions of (2+1)-dimensional time-fractional Zoomeron equation - Aksoy, Esin; Cevikel, Adem C.; Bekir, Ahmet (ELSEVIER GMBH, 2016)
In this article, a new application of sub-equation and generalized Kudryashov methods has been used for solution of nonlinear (2+1)-dimensional time fractional Zoomeron equation with modified Riemann-Liouville derivative. For this, the fractional complex transformation has been used to convert fractional differential equation to ordinary differential equation of integer order. As a result, two types of exact analytical solutions have been obtained. (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: Exact solutions; Time fractional Zoomeron equation; Fractional complex transformation; Modified Riemann-Liouville derivative; Sub-equation method; Generalized Kudryashov method; PARTIAL-DIFFERENTIAL-EQUATIONS; FUNCTIONAL VARIABLE METHOD; FINDING EXACT-SOLUTIONS; Optics